Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1590/s0066-782x2010000300011
|View full text |Cite
|
Sign up to set email alerts
|

Estimulação elétrica nervosa transcutânea de curta duração no pós-operatório de cirurgia cardíaca

Abstract: Background: Respiratory muscle strength has been related to the postoperative outcome of cardiac surgeries. The main documented therapeutic purpose of transcutaneous electrical nerve stimulation (TENS) is the reduction of pain, which could bring secondary benefits to the respiratory muscles and, consequently, to lung capacities and volumes.Objectives: The objective of the present study was to evaluate the effectiveness of short-duration transcutaneous electrical nerve stimulation (TENS) in the reduction of pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
0
10
0
12
Order By: Relevance
“…Transcutaneous electrical nerve stimulation (TENS) is a noninvasive technique that is effective for postoperative pain management [ 8 , 9 ]. It has been demonstrated to produce effective analgesia and reduce postoperative opioid requirements in patients undergoing cardiac surgery, and it has no side effects [ 10 ]. It is a comfortable, noninvasive, and nonpharmacological method, which can be easily performed.…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS) is a noninvasive technique that is effective for postoperative pain management [ 8 , 9 ]. It has been demonstrated to produce effective analgesia and reduce postoperative opioid requirements in patients undergoing cardiac surgery, and it has no side effects [ 10 ]. It is a comfortable, noninvasive, and nonpharmacological method, which can be easily performed.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, the effects of TENS have been studied on acute and chronic pain. Some studies were extended to also benefit the algesic processes occurring in the postoperative period [25].…”
Section: Discussionmentioning
confidence: 99%
“…Gregorini et al . [23] reported that patients in post operatory of cardiac surgery showed decreased volumes and pulmonary capacities, therefore reducing the quantity of deep inspirations and cough effectiveness. The lessening of deep inspiration and cough has been proposed to predispose respiratory complications in which atelectasis is the most frequent, reaching approximately 64% of operated patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…To analyze data normality Kolmogorov-Smirnov test was applied. Since data was regularly distributed the correlation assessment between DVC measured with ventilometer and incentive inspirometer was based on Pearson correlation coefficient [23,25]. T-student test for independent samples was used to compare patients' variables in pre and post operatory periods.…”
Section: Methodsmentioning
confidence: 99%